Profil Literasi Keuangan Pada Mahasiswa Program Studi Pendidikan Guru Pendidikan Anak Usia Dini Universitas Negeri Medan - Elvi Meirani Br Surbakti; Srinahyanti Srinahyanti (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
The existence of financial literacy helps individuals make smarter purchases, for example by thinking about the needs that need to be met, the price of products, services and services provided. Good financial literacy facilitates thinking in making decisions, especially in the financial sector. Because in this case they are considered capable of reading or assessing and considering the current financial situation. Financial literacy is needed not only in personal life, but also in work, especially those that are closely related to financial activities. In the family itself, good financial literacy usually has to be carried out by the head of the family or other family members such as the mother. If the family lacks people who have good financial literacy, then the family's spending or consumption may not be commensurate with the income earned in the family, so it can be said that there is a lack of money to meet the family's living needs. This can also happen in social life. It could also be said that if we have good financial literacy, we cannot manage our expenses well.